The Jumble Word Game and Its Effect on Vocabulary Mastery - Nauli Rangkuti, Bunga Rizky; Lubis, Fitriadi; Royani, Ida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to: (1) determine students' vocabulary mastery before learning using jumble word game. (2) determine students' vocabulary mastery after learning using jumble word game. (3) determine whether or not there is a significant effect of jumble word game on vocabulary mastery. This quantitative research employed a pre-test post-test control group design. The population was grade VIII students of SMP N 8 Padangsidimpuan, with 60 students as a sample. A multiple choice was used as instrument. The experimental group's average score increased from 56.73 (pre-test) to 80.07 post-test), indicating a shift from the